Zoonoses in the margins: environmental displacement and health outcomes in the Indus Delta - Dorien H. Braam (BMC, 2022)
Abstract Background It remains unclear how human and animal displacement impacts zoonotic disease risk with little contextualized primary data available. This study investigates zoonotic disease dynamics in populations regularly displaced due to slow onset disasters and annual monsoons in the Indus Delta in Sindh province in southeast Pakistan. Methods Using a case study methodology, semi-structured key informant interviews and focus group discussions with 35 participants, as well as observational studies were conducted in seven communities in Thatta district. Results Key factors affecting zoonotic disease dynamics in environmental displacement in Thatta identified in the study include disasters and loss of forage, a lack of veterinary and healthcare access, and socio-economic status. Animal and human health are an important consideration in displacement disrupting communities and livelihoods, affecting safety, health, and food security. Displacement results in a poverty spiral whereby the displaced find themselves at continuous peril from poverty and disaster, with zoonotic disease dynamics shifting based on environmental changes, and an expectation of future movement and loss. Conclusion The precarious conditions generated through the disruption of communities and livelihoods makes environmentally displaced populations vulnerable to zoonotic disease. To prevent further displacement and disease, broader political economy issues need to be addressed, and comprehensive assistance provided to support sustainable livelihoods.